Filsafat Pendidikan Kejuruan: Kontribusinya terhadap Pengembangan Kebijakan Pendidikan Berbasis Kompetensi - Novri Wahyuni; Ernawati Ernawati; Jonni Mardizal (Mathematics Education Study Program, 2025)
The philosophy of vocational education plays a crucial role in supporting the development of competency-based education policies, especially in creating graduates who are ready to face the demands of the world of work. This study uses a literature study method to explore the contribution of the philosophy of vocational education in building relevant, responsive, and equitable education policies. This study identifies several important elements, including the integration of theory and practice, collaboration with the industrial world, and adaptation to the needs of a dynamic labor market. The findings show that the philosophy of vocational education not only supports the development of competency-based curricula but also provides an ethical basis for making educational policy decisions. The results of this study confirm that an approach based on the philosophy of vocational education is able to encourage improvements in the quality of human resources while strengthening global competitiveness. This article recommends the importance of the philosophy of vocational education as a strategic reference in designing vocational education policies, especially in vocational schools, to ensure compliance with the needs of industry and society.